UPAYA PENCEGAHAN SKABIES MELALUI PENYULUHAN PERSONAL HYGIENE DI PONDOK PESANTREN TARBIYATUL MUSTAFID KECAMATAN NARMADA - Supriyadi, Supriyadi; Muhammad Aozai; Dewi Nur Sukma Purqoti; Syamdarniati (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2024)
Islamic boarding schools, as educational institutions that adopt a dormitory system, are one of the environments that are very vulnerable to the spread of scabies. Overcrowding conditions, poor personal hygiene, and limited sanitation facilities are the main factors that increase the risk of spreading this disease among students. Purpose: This service activity aims to increase the knowledge of students in prevention Purpose: This service activity aims to increase the knowledge of students in the prevention of scabies. Method: The community service method is carried out in the form of health counseling on how to prevent scabies disease with lectures and questions and answers. Result: Personal hygiene counseling is an effective preventive effort to prevent the spread of scabies in Islamic boarding schools.